Pengaruh Audit Operasional dan Pengendalian Internal Terhadap Kinerja Karyawan pada PT BPR Gemilang (Perseroda) Kabupaten Indragiri Hilir - SUNARTI SUNARTI; RANTI MELASARI; BADEWIN BADEWIN (Fakultas Ekonomi Universitas Islam Indragiri, 2026)
This study examines the effect of operational audit and internal control on employee performance at PT BPR Gemilang Perseroda Indragiri Hilir. The research is motivated by the need to improve employee performance to support effective and accountable banking operations. The research aims to analyze the influence of operational audit and internal control on employee performance. This study uses a quantitative approach with a survey design. The population consists of all employees of PT BPR Gemilang Perseroda, totaling 30 respondents, using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results show that operational audit and internal control have a positive and significant effect on employee performance, both partially and simultaneously. These findings indicate that effective audit implementation and strong internal control can improve work quality and productivity. In conclusion, strengthening operational audit and internal control is essential to enhance employee performance in regional banking institutions.